Analisis Pelaksanaan Supervisi Guru Sekolah Dasar di Kecamatan Indralaya Utara Kabupaten Ogan Ilir - Arfa'i, Muslim; Zuber, Konar; Hestirinaih, Deby Chintia (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
Supervision is an academic activity that involves monitoring by someone with higher and deeper knowledge and a keen sensitivity to understanding the object of their work with a clear mind. The issues identified through observation by the researcher include a lack of teachers' understanding of the implementation of supervision, inadequate supervisory oversight by the school principal, limited facilities and infrastructure at the school, teachers lacking the skills or competence to develop learning materials, the failure of teachers to use lesson plans (RPP) that reflect the design of learning activities, the continued use of conventional teaching methods, and low teacher education qualifications, which result in poor teacher quality.The purpose of this research is to identify, describe, and analyze the implementation of supervision of elementary school teachers in North Indralaya Subdistrict, Ogan Ilir Regency. This study is descriptive research with a qualitative approach. The results of the research show fairly good outcomes; goal-setting is currently being conducted in line with the guidelines provided by the Minister of Education and Culture Regulation No. 40 of 2021, implemented through socialization by providing guidance and direction on the preparation of learning materials, learning implementation, and learning evaluation through discussion meetings. However, the facilities and infrastructure that support the supervision of elementary school teachers are still inadequate, as some equipment, such as laptops and projectors, is limited to only two units each, making it difficult for teachers to apply them in the classroom. Additionally, there is a lack of uniform supervisory oversight conducted by the principal and supervisors for teachers at SD Negeri 19 and SD Negeri 6 in North Indralaya Subdistrict, Ogan Ilir Regency.